Characterization of poxtA, a novel phenicol–oxazolidinone–tetracycline resistance gene from an MRSA of clinical origin. (4th April 2018) - Antonelli, Alberto; D'Andrea, Marco Maria; Brenciani, Andrea; Galeotti, Cesira L; Morroni, Gianluca; Pollini, Simona; Varaldo, Pietro Emanuele; Rossolini, Gian Maria
Abstract: Objectives: To characterize a novel phenicol–oxazolidinone–tetracycline resistance gene, named poxtA, identified in a previously described MRSA strain that was highly resistant to linezolid and also carried the cfr gene. Methods: The poxtA gene was identified by bioinformatic analysis of the whole genome sequence of Staphylococcus aureus AOUC-0915. The poxtA gene was cloned in a shuttle plasmid vector and expressed in Escherichia coli, S. aureus and Enterococcus faecalis to investigate the protein function. Comparative sequence analyses at the protein and genetic levels were carried out using standard procedures. Results: The poxtA gene encodes a protein that is 32% identical to OptrA and exhibits structural features typical of the F lineage of the ATP-binding cassette (ABC) protein superfamily that cause antibiotic resistance by ribosomal protection. Expression of poxtA in E. coli, S. aureus and E. faecalis was able to decrease susceptibility to phenicols, oxazolidinones and tetracyclines. A database search identified the presence of poxtA in E. faecalis, Enterococcus faecium and Pediococcus acidilactici strains, mostly of animal origin, and revealed the presence of poxtA homologues in the genomes of some Clostridiales. Analysis of the genetic context revealed that poxtA was located in a composite transposon-like structure containing two IS 1216 elements. Conclusions: A novel resistance gene, named poxtA, encoding a protein of the antibiotic resistance (ARE) ABC-F lineage, was identified in the genome of an MRSA of clinical origin. PoxtA can confer decreased susceptibility to phenicols, oxazolidinones and tetracyclines and is associated with a putative mobile element that could contribute to its horizontal dissemination.